The Relationship Of The Quality Of Antenatal Care (Anc) Services With The Level Of Pregnant Women's Satisfaction - Asmima Yanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to explore the relationship between the quality of antenatal care (ANC) services and the satisfaction levels of pregnant women at the Kuta Raja Community Health Center, Banda Aceh. This relationship is pivotal in understanding how service quality impacts maternal satisfaction and, ultimately, maternal health outcomes. Maternal Mortality Rate (MMR) is defined as the number of mothers who die during postpartum, pregnancy, and childbirth. High MMR is often attributed to a lack of awareness and infrequent ANC visits. In 2023, only 86.25% of pregnant women attended ANC services, falling short of the 93% target. Initial observations indicated that 60% of the attendees were dissatisfied with the ANC services at the Kuta Raja Community Health Center. This analytical survey, employing a cross-sectional design, was conducted at the Kuta Raja Community Health Center. The study population included 93 pregnant women, all of whom were surveyed using a total sampling technique. Data were analyzed using univariate and bivariate analyses, with the chi-square test employed for bivariate analysis. The study found that certain quality dimensions of ANC services—responsiveness (p < 0.001), assurance (p < 0.005), empathy (p < 0.005), and tangibility (p < 0.001)—were significantly related to the satisfaction levels of pregnant women. However, reliability (p > 0.05) showed no significant relationship with satisfaction. There is a significant relationship between the responsiveness, assurance, empathy, and tangibility of ANC services and the satisfaction levels of pregnant women at the Kuta Raja Community Health Center. Conversely, reliability did not show a significant correlation with satisfaction. To improve maternal satisfaction and health outcomes, it is recommended that pregnant women regularly attend ANC services and that efforts be made to enhance the quality dimensions that impact satisfaction.